Let $X$ and $Y$ be independent and identically distributed $(i.i.d.)$ r.v.’s, each having the probability distribution, $p(k) = (1 − λ)λ^k$; $k = 0,1,...$ where $λ :(0; 1)$ is a constant. Define $U = min(X; Y )$; $V = max(X; Y )$; $W = V − U$. Determine the joint probability distribution of $U$ and $W$ (taking care with $W = 0$) and verify that $U$ and $W$ are independent r.v.’s.

My work: I set up this: $P(X=W+U, Y=U)$ when $X>Y$ and $P(X=U, Y=W+U)$ when $X<Y$. and the joint distributions are the same in both cases as $W$ is always non-negative. finally I got the following joint pmf: $f(w,u)=(1-λ)^2 λ^(w+2u-2)$ when $X=Y$, $f(w,u)=(1-λ)^2 λ^(2u-2)$ and ${(w,u): w=0,1...; u= 0,1,..}$ is this the correct joint pmf? what will be the final joint pmf?

  • $\begingroup$ What did you try? If this is some sort of an assignment, consider adding the self-study tag and read the tag wiki. $\endgroup$ – StubbornAtom Oct 18 '18 at 7:16
  • $\begingroup$ Your $W$ is just $|X-Y|$. This might help: math.stackexchange.com/questions/2685256/… $\endgroup$ – StubbornAtom Oct 18 '18 at 7:33
  • $\begingroup$ I saw your mentioned problem. I have solved that problem from Casella and Burger. But in this particular problem, isn't W is always greater than or equal to 0? $\endgroup$ – Dihan Oct 18 '18 at 8:11
  • $\begingroup$ Yes, of course $W$ is non-negative. I was thinking about breaking the problem into cases $X\ge Y$ and $X<Y$. $\endgroup$ – StubbornAtom Oct 18 '18 at 8:17
  • $\begingroup$ I set up this: $P(X=W+U, Y=U)$ when $X>Y$ and $P(X=U, Y=W+U)$ when $X<Y$. and the joint distributions are the same in both cases as $W$ is always positive $\endgroup$ – Dihan Oct 18 '18 at 8:18

Both values of $U$ and $W$ are non-negative integers, say $u$ and $w$ respectively. We need to find which values of $(x,y)$ are associated with $(u,w).$ This is tantamount to solving the simultaneous equations

$$\begin{array}{rl} \min(x,y) &=u \\ \max(x,y)-\min(x,y)&=w \end{array}$$

for $(x,y).$ There are two possibilities: $\min(x,y)=x$ or $\min(x,y)=y.$ In the first case, $x=u$ whence $y=u+w.$ In the second case $y=u$ whence $x=u+w.$ These cases overlap when $w=0,$ which occurs when $X=Y.$

Therefore, by the probability axioms, when $w\ne 0$

$$\Pr((U,W)=(u,w)) = \Pr((X,Y)=(u,u+w)) + \Pr((X,Y)=(u+w,u))$$

and otherwise when $w=0$

$$\Pr((U,W)=(u,0)) = \Pr((X,Y)=(u,u)).$$

The independence of $X$ and $Y$ means their probabilities multiply, immediately giving

$$\eqalign{ \Pr((U,W)=(u,w)) &= \left\{\begin{array}{rl}(1-\lambda)\lambda^u\,(1-\lambda)\lambda^{u+w} + (1-\lambda)\lambda^{u+w}\,(1-\lambda)\lambda^u & \text{if }w\ne 0 \\ (1-\lambda)\lambda^u\, (1-\lambda)\lambda^u &\text{if } w=0\end{array}\right. \\ &= (1-\lambda)^2\lambda^{2u+w}\left\{\begin{array}{rl}2 & \text{if }w\ne 0 \\ 1 &\text{if } w=0.\end{array}\right. }$$

A convenient way to write that last expression in brackets uses the binary indicator function $\mathcal{I}:$

$$\mathcal{I}(w\ne 0) + 1 = \left\{\begin{array}{rl}2 & \text{if }w\ne 0 \\ 1 &\text{if } w=0.\end{array}\right.$$


$$\Pr((U,W)=(u,w)) = (1-\lambda)^2\ \left(\color{blue}{\lambda^{2u}}\right)\ \left(\color{red}{\left(\mathcal{I}(w\ne 0) + 1\right)\lambda^w}\right).$$

This is a product of a normalizing constant $(1-\lambda)^2,$ a function of $u$ alone (in blue), and a function of $w$ alone (in red), demonstrating $U$ and $W$ are independent.

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.